[PP.09.07] AMBULATORY BLOOD PRESSURE BEHAVIOUR IN END STAGE RENAL DISEASE PATIENTS UNDERGOING HAEMODIALYSIS. (September 2016) - Kasiakogias, A.; Tsioufis, C.; Dimitriadis, K.; Andrikou, E.; Konstantinidis, D.; Chatzis, D.; Aragiannis, D.; Lagiou, F.; Peskesis, G.; Roussos, D.; Tousoulis, D.
Abstract : Objective: Blood pressure (BP) evaluation and management in patients with end stage renal disease (ESRD) is a precarious matter. During hemodialysis (HD) hypotension as well as a paradoxical rise in BP may be documented. We investigated circadian BP behavior in the setting of ESRD. Design and method: We studied 19 patients with ESRD (68% men, mean age 62 ± 19 years, 52% hypertensive) that underwent HD three times a week in the HD unit of our hospital. Ambulatory blood pressure monitoring was applied one hour before an HD session and was set to measure BP every 30 minutes and until arrival for the next HD session, for a total of two subsequent 24-hour periods. Dipping was defined as (daytime systolic BP – nighttime systolic BP)/ daytime systolic BP. Results: Body weight before and after the HD session was 78 ± 28Kgr and 75 ± 27mmHg respectively. Clinic systolic/diastolic BP before the HD session was 133 ± 23/66 ± 11mmH and at the end was 126 ± 25/69 ± 12mmHg. Four patients (21%) exhibited intradialytic hypertension defined as a systolic BP increase > or = 10 mmHg from pre- to post HD. Ambulatory systolic/diastolic BP increased not significantly from 127 ± 23/70 ± 13 mmHg to 130 ± 19/71 ± 11mmHg from the first to the second 24-hour period. Increases were also non-significant for daytime and nighttime BP (128 ± 22 mmHg vs 129 ± 19 mmHg and 126 ± 25 mmHg vs 131 ± 21 mmHg respectively, p > 0.05). Mean dipping was 1.5 ± 7.8% in the first day and further decreased to −0.94 ± 6.8% in the second day. Accordingly, in the first 24-hour period, only 3 patients (16%) were dippers and reduced to 1 patient in the following day (5%). Eight patients (42%) and 9 patients (47%) were risers at the first and second 24-hour period respectively. Conclusions: Daytime systolic BP does not substantially change during the 48-hour period extending from HD to HD session. Yet, a non-dipper as well as a riser pattern are highly prevalent and increase during the interdialytic period.